Exchange reserves and the financial structure of foreign trade - Grassman, Sven (Farnborough : Saxon House, [Lexington, Mass.] : Lexington Books, 1973)
This book contains an investigation of capital movements associated with shifts in the timing of payments for current account transactions in the Swedish balance of payments. The study grew out of the work within the Swedish Ministry of Finance relating to the whole international payments structure in Sweden, and in particular to the balancing errors and omissions item in the balance of payments statistics. This item proved to be decisive in terms of the overall payments situation on several occasions in the late 1960s, and it was thought to contain large and rapidly fluctuating commercial capital movements.
Includes index.
Bibliography: p. 189-193.
usc 08/05/18; 22/05/18
Loans
Keywords: Foreign exchange; Balance of payments; International trade